Cycloplegic Effects on the Cylindrical Components of the Refraction - Athar Zareei; Milad Abdolahian; Shahram Bamdad (Journal of Ophthalmology)
It is important to predict which astigmatic patients require separate refraction for near vision. This study compared cylindrical components changes by cyclopentolate 1% for the low and high amount of astigmatism. The right eyes of 1014 healthy individuals (307 males and 707 females) with cylindrical refractive power more than −0.5 diopter on autorefractometer were selected. Both male and female patients in the age range of 17–45 years were refracted before and after cycloplegia, using 1% cyclopentolate. All volunteers were classified into 2 subgroups including the lower astigmatism group (−2.25 to −0.50) and the higher astigmatic group (−2.50 to over). Alpines’ method was used to compare the effect of cycloplegic drop on cylindrical power. The mean age in the lower astigmatism group (29.58; 95% CI: 29.18 to 29.99 years) was not significantly different from the higher astigmatic group (29.85; 95% CI: 29.07 to 30.62) and there were no significant differences in gender between these two groups (P=0.54). Differences between wet and dry refraction in J0 (−0.03; 95% CI:−0.06 to −0.008) and J45 (−0.03; 95% CI:−0.06 to −0.01) were significant only in the higher astigmatic group. Axis changes by the cycloplegic drop in the lower astigmatism group were 3.51 (CI: 3.22 to 3.81) and axis changes by the cycloplegic drop in the higher astigmatism group were 2.21 (CI: 1.73 to 2.49). In patients with a lower amount of astigmatism (−2.25 to −0.50), additional near subjective refraction could be done for precise determination of axis and in patients with a higher amount of astigmatism (−2.50 to over), near subjective refraction might be done for precise determination of power.